2017
DOI: 10.1016/j.dadm.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL‐8 is a marker of white‐matter hyperintensities in patients with Alzheimer's disease

Abstract: IntroductionNeuroinflammation and cerebrovascular disease (CeVD) have been implicated in cognitive impairment and Alzheimer's disease (AD). The present study aimed to examine serum inflammatory markers in preclinical stages of dementia and in AD, as well as to investigate their associations with concomitant CeVD.MethodsWe performed a cross-sectional case–control study including 96 AD, 140 cognitively impaired no dementia (CIND), and 79 noncognitively impaired participants. All subjects underwent neuropsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 48 publications
5
30
0
Order By: Relevance
“…A recent study showed that serum IL-8 concentrations were associated with (Fig. 2 WMH on T2-weighted MRI in patients with AD [50]. The present study adds evidence that peripheral IL-8 concentrations in AD might partly indicate neutrophil chemoattractant and activator functions, which predict a decline in executive function.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study showed that serum IL-8 concentrations were associated with (Fig. 2 WMH on T2-weighted MRI in patients with AD [50]. The present study adds evidence that peripheral IL-8 concentrations in AD might partly indicate neutrophil chemoattractant and activator functions, which predict a decline in executive function.…”
Section: Discussionsupporting
confidence: 70%
“…46,47 WMH might be a consequence of neuroinflammation. 48 Our neuropathology data showed high agreement between our clinical diagnosis and the definitive pathologic diagnosis. Although our data showed that 100% of homozygous APOE e4 carriers had CAA compared to 64% of heterozygotes, it did not show that WMH burden was associated with worse cognition in people with 2 alleles, and should be interpreted with caution due to the small sample size.…”
Section: Discussionsupporting
confidence: 68%
“…Transient cognitive impairment was most prevalent in the first week post-stroke (39%) compared with after this week (19%) [21]. It was found that the serum level of IL-8 was significantly elevated in the plasma of the patients in the first 48 h post stroke in comparison to control group in this study which was in concordance with [6,22]. This could be attributed to the fact that astrocytes induce IL-8 expression in the area of brain damage.…”
Section: Discussionsupporting
confidence: 82%